(untitled) (Nexo Revista Científica, 2023)
The purpose of the article is to develop theoretical provisions and methodological support for assessing the competitiveness of tourist services as the basis of a tourist destination. And the methods of factor analysis, the method of multi-criteria assessment, the correlation-regression method, the methods of indicative planning and economic and mathematical modeling were used. Some problems have been solved using comparison and linear optimization methods. The article explores theoretical and methodological approaches to the evaluation of tourist services in a constantly changing competitive environment and the actualization of new technologies. The methods of assessing and transforming the quality and increasing the competitiveness of tourist services within the regional recreation and tourism market were studied using the example of the Republic of Tatarstan, which predetermined the relevance of the stated topic, the purpose of the study and the tasks set. The practical value is confirmed by the possibility of using the results obtained in the development strategy of tourist organizations by regional government bodies, as well as in the activities of federal and regional tour operators.